THE GREEN-FUNCTION IN THE BLOCH-NORDSIECK MODEL FOR QED(3) - Pimentel, B. M.; Tomazelli, J. L. (Iop Publishing Ltd, 1994)
The electron Green's function is obtained in the Bloch-Nordsieck approximation of three-dimensional QED. Dimensional regularization is used in the intermediate stages of calculation.